A(o) enfermeira(o) na estratégia saúde da família: percepção sobre o cuidado às pessoas LGBT+ - Silveira, Walkiria Jessica Araujo (2023)
Care for the LGBT+ population has as its fundamental aspect the influence of the professional's vision in the provision of care and the need for adequate reception, as these people already arrive at health services stigmatized, due to prejudiced situations that they experience on a daily basis. Objective: To analyze the perception of ESF nurses about health care for LGBT+ people. Method: This is a descriptive study, with a qualitative approach. Data were collected in May and June 2023, through semi-structured interviews with nurses from the ESF in the city of São Luís/MA. The information obtained was analyzed through content analysis through processing in the IRAMUTEQ software. The project was approved by the Research Ethics Committee of the Federal University of São Carlos/UFSCar, CAAE 66695223.4.0000.5504, opinion no. 5,946,479 and authorization by the Municipal Health Department of the city of São Luís/MA through the letter of consent. Results: 31 nurses participated in the study, the majority of whom were cis women (93.5%), aged between 26 and 55 years old, married (68.8%) and mixed race (64.5%), with time of professional experience in the ESF between 8 months and 28 years. Two categories emerged from the Descending Hierarchical Classification (CHD), identified by subcorpus A and B, being A) Facilities and difficulties in assistance and B) Primary Health Care and professional satisfaction. Final considerations: It is possible to analyze the perception of ESF nurses about health care for LGBT+ people with the aim of proposing strategies to improve care, taking into account the facilities and mainly focusing on the difficulties presented by professionals who provide this assistance in PHC.